MENINGKATKAN KEMAMPUAN MEMBACA MELALUI STORYTELLING PADA ANAK DI TK ISLAM BINA EMPAT LIMA PONTIANAK - Sri Astuti; Sri Lestari; Desni Yuniarni (Universitas Tanjungpura, 2019)
AbstractThe background of this research is that there are still many students who have not been able to match simple writing with symbols that represented it, students who have not been able to say simple writing with symbols that represented it and students who have not known various types of vowel letters and consonants . The form of this research is Classroom Action Research. This research was conducted with a qualitative research approach. The subjects in this study were: 1) Children of Islamic Kindergarten Four Development Five groups B6 which numbered twenty one people; and 2) two kindergarten Islamic Kindergarten Teachers. Data collection techniques use observation techniques. Data collection tool: a) Child learning observation sheet; b) Instrument sheet for assessing the teacher's ability to plan learning; and c) The instrument sheet assesses the teacher's ability to carry out learning. Storytelling learning is carried out through three cycles and in each cycle occurs using different themes and sub-themes referring to the 2013 curriculum; The results of the implementation of storytelling learning can improve children's reading skills so that children can mention and connect simple writing with images that symbolize it and are able to recognize various kinds of consonants and vowels. Keywords: Early Childhood, Reading Ability, and Storytelling